The prevalence of human papillomavirus in cervical lesions with koilocytosis and/or CIN I. - Iversen, A; Duun, S; Sebbelov, A; Norrild, B (1992)
Thirty-one patients with koilocytosis and/or concomitant CIN I were analysed for the presence of HPV types 11, 16 and 18 by in situ hybridization and Southern blot analysis. The prevalence of HPV was 48% and 55%, respectively, when measured by the two methods and among the HPV positive, HPV 11 and 16 were present in 47% and 60%, respectively, whereas HPV 18 was not found.